Pendampingan Perlindungan Hukum Pelayanan Kesehatan Melalui Informed Consent - Arista Candra Irawati; Wahyu Kristiningrum; Ari Andayani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2020)
The community considers health services in particular medicine to be a " therapeutic miracle" (miracle), but it must be remembered that medical treatment contains a "therapeutic risk" , which may be the risk of the patient, or the risk of the doctor / midwife or both parties bear the risk, tends rated malpractice. Through informed consent as a communication process followed by a statement of agreement from the patient that is given freely and rationally, the community considers that the assessment of health services is not optimal, the lack of understanding / communication between doctors / midwives and patients in carrying out their duties in efforts to restore health can be avoided. Through i Hopefully this partnership activity, PKK mothers who take part in this Assistance activity will know more, understand and are motivated to get professional health services , avoid legal problems / malpractice. In the implementation of community service activities, this is carried out using a participatory approach method, meaning that the participants are required to be active in participating during the activity. The competencies that will be formed are marked by indicators of increasing participants' knowledge about legal understanding of the importance as a form of the right to health services, as a protected human right, in the law . Results Assessment of q uisinoner pre-test and post-test, the answers p ara cadres has increased significantly , in which all participants were able to answer all questions q uisinoner post test really all it means that the entire cadre of very enthusiastic and barsungguh serious in following the process of the activities of community service this .Â Through this partnership activity, it is hoped that the PKK (Health / Pokja) cadres in Langensari Village who participate in this assistance will know more, understand and are motivated to be able to implement and receive maximum health services in order to avoid losses leading to legal issues that lead to the court process level. and able to provide counseling to community members in Langensari Village, West Ungaran District, Semarang RegencyAbstrakMasyarakat menganggap pelayanan kesehatan pada khususnya pengobatan merupakan suatu â€therapeutic miracleâ€ (mujijat), namun harus diingat bahwa tindakan medis itu mengandung suatu â€therapeutic riskâ€, yang dimungkinkan menjadi resiko pasien, atau resiko Dokter/Bidan ataukah kedua belah pihak menanggung resiko,cenderung dinilai malpraktek. Melalui Informed consentsebagai proses komunikasi yang diikuti pernyataan setuju dari pasien diberikan dengan bebas dan rasional, maka penilaian pelayanan kesehatan dinilai belum maksimal oleh masyarakat, kurangnya pemahaman/komunikasi antara Dokter/Bidan dengan pasien dalam menjalankan tugasnya dalam upaya pemulihan kesehatan dapat terhindarkan. Melalui kegiatan kemitraan ini diharapkan, para ibu-ibu PKK yang mengikuti kegiatan Pendampingan ini akan lebih mengetahui, memahami dan terdorong untuk mendapatkan pelayanan kesehatan yang professional,terhindar dari persoalan hukum/malpraktek. Dalam pelaksanaan kegiatan pengabdian pada masyarkat ini dilaksanakan dengan metode pendekatan partisipatif artinya para peserta dituntut aktif dalam mengikuti selama kegiatan berlangsung. Kompetensi yang akan dibentuk ditandai dengan indikator peningkatan pengetahuan peserta tentang Pemahaman hukum tentang pentingnya sebagai wujud hak memperoleh pelayanan kesehatan, sebagai hak asasi yang dilindungi, di dalam Undang-Undang. Hasil Penilaian dari quisinoner pre test dan post test, jawaban para kader mengalami peningkatan yang signifikan, dimana seluruh peserta dapat menjawab seluruh pertanyaan quisinoner post test betul semua artinya bahwa seluruh kader sangat antusias dan barsungguh-sungguh dalam mengikuti proses kegiatan pengabdian masyarakat ini. Melalui kegiatan kemitraan ini diharapkan, Kader PKK (Kesehatan/Pokja) di Kelurahan Langensari yang mengikuti pendampingan ini akan lebih mengetahui, memahami dan terdorong untuk dapat menerapkan, menerima pelayanan kesehatan secara maksimal agar terhindar dari kerugian mengarah kepada persoalan hukum yang membawa ke tingkat proses Pengadilan serta mampu memberikan penyuluhan ke warga masyarakat di Kelurahan Langensari Kecamatan Ungaran Barat, Kabupaten Semarang